Read this before our next meeting - Pittampali, Al. (Michigan Brilliance Audio, 2011)
One mediocre meeting after another quietly corrodes our organization, and every day we allow it to happen. Culture change occurs when a transformational idea spreads to enough people. Like a virus that makes its way from person to person, spreading exponentially faster, so can the Modern Meeting. The status quo must go. Now. Before it's too late.